2023
DOI: 10.2174/011570162x271199231128092621
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Traditional Chinese Medicine in the Intervention and Treatment of HIV while Considering its Safety and Efficacy

Mohamad Hesam Shahrajabian,
Wenli Sun

Abstract: Natural products have been considered a potential resource for the development of novel therapeutic agents, since time immemorial. It is an opportunity to discover cost-effective and safe drugs at the earliest, with the goal to hit specific targets in the HIV life cycle. Natural products with inhibitory activity against human immunodeficiency virus are terpenes, coumarins, flavonoids, curcumin, proteins, such as lectins, laccases, bromotyrosines, and ribosome-inactivating proteins. Terpenes inhibit virus fusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 220 publications
0
2
0
Order By: Relevance
“…All the bromotyrosine derivatives isolated before 2004 were thoroughly reviewed in 2005 by J. Peng et al [ 4 ]. Moreover, bromotyrosines have been extensively researched, with a total of 24 reviews published covering various aspects related to bromotyrosines, including their biological effects [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ], their roles in biological processes [ 16 ], and synthetic methodologies [ 17 ]. Our review comprehensively covers newly identified bromotyrosines from 2004 to 2023, examining both their structural features and related activities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…All the bromotyrosine derivatives isolated before 2004 were thoroughly reviewed in 2005 by J. Peng et al [ 4 ]. Moreover, bromotyrosines have been extensively researched, with a total of 24 reviews published covering various aspects related to bromotyrosines, including their biological effects [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ], their roles in biological processes [ 16 ], and synthetic methodologies [ 17 ]. Our review comprehensively covers newly identified bromotyrosines from 2004 to 2023, examining both their structural features and related activities.…”
Section: Introductionmentioning
confidence: 99%
“…They differ by the type of connections, the nature of the side chains, and the substitution patterns of the aromatic rings. In 1995, J. R. Carney and K. L. Rinehart investigated the biosynthesis of bromotyrosine derivatives by the marine sponge Aplysina fistularis using 14 C-labeled amino acids such as 14 C-L-Tyrosine, 14 C-L-3-bromotyrosine, and 14 C-L-3,5-dibromotyrosine. This study revealed that the bromotyrosine unit (3) of bromoisoxazoline alkaloids originated from phenylalanine, which was then converted to tyrosine (Figure 1) [5].…”
Section: Introductionmentioning
confidence: 99%